AN EXAMPLE ANALYSIS ON THE LINGUISTIC STRATEGIES USED IN OP-ED ARTICLES - Meltem SARGIN (Fırat University, 2019)
The concrete products of discourse, which can be defined as a social practice that reflects the ideology of the social section it belongs to, are texts that are produced orally or in written form. By making linguistic analyses within the framework of Critical Discourse Analysis it is possible to expose the implicit ways of loading ideology in texts (Sargın, 2010, s. 64). Op-ed articles are a good example for the reproduction of ideology through language as a social practice. These articles generally express ideas that differ according to the type and the ideology of newspapers (Van Dijk, 1998, s. 21). They defend the ideas they put forth within the frame of the ideology they belong to (Yağcıoğlu, 2002, s. 124). In this line of reasoning, this study aims to find out how the same topic is structured on the linguistic plane by the op-ed articles published in newspapers from different ideological orientations, thus revealing the relationship between language and ideology. As the corpus of the study op-ed articles produced in the context of the Gezi Park protests were selected from three newspapers believed to represent different ideologies namely left, liberal, and conservative ideologies. As the result of the analysis, it is seen that the linguistic choices made in the op-ed articles serve the ideologies of the writers, and thus of the newspaper they represent. Besides, the study is of importance in serving as a plain model for the implementation of Critical Discourse Analysis.